Proteomics analysis of somatic embryogenesis in oil palm (Elaeis guineensis Jacq) - Tan, Hooi Sin (2016)
Oil palm is an important commercial crop in Malaysia where Malaysia is the second largest producer and exporter of palm oilin the world. In order to meet the increasing demand for palm oil, elite oil palm planting materials with higher palm oil yield are the desirable planting materials. Hence, the oil palm plantation companies have incorporated in vitro micropropagation technique through somatic embryogenesis in producing elite oil palm. However, low embryogenesis rate has hampered large production of elite oil palm ramets. In this study, proteomic technology was deployed to compare protein expression and identify differential expressed protein between high and low proliferated embryogenic lines of oil palm tissue culture. From the study, total protein of oil palm young and old leaves was extracted using an optimized trichloroacetic acid/acetone precipitation protocol followed by polyethylene glycol (PEG) fractionation to isolate low abundance proteins. Then, the extracted proteins were separated on two-dimensional (2D) gel electrophoresis and protein profiles between the high and low proliferated embryogenic lines were compared. Total of 40 differentially expressed protein spots were isolated from the 2D gel for mass spectrophotometry (MS/MS) identification. However, only 26 out of 40 protein spots were identified and just 8 of the identified protein spots were isolated from young leaves. Quantitative real-time PCR were conducted on 17 proteins candidates to study on the relationship between the protein and mRNA expression level. There was 29% of the 17 proteins’ expression showed linear correlation with their mRNA expression. These proteins candidates were highlighted for further validation in the future.